Sindbis Virus-Induced Neuronal Death Is both Necrotic and Apoptotic and Is Ameliorated by N-Methyl-d-Aspartate Receptor Antagonists - Nargi-Aizenman, Jennifer L. (American Society for Microbiology, 2001)
Virus infection of neurons leads to different outcomes ranging from latent and noncytolytic infection to cell death. Viruses kill neurons directly by inducing either apoptosis or necrosis or indirectly as a result of the host immune response. Sindbis virus (SV) is an alphavirus that induces apoptotic cell death both in vitro and in vivo. However, apoptotic changes are not always evident in neurons induced to die by alphavirus infection. Time lapse imaging revealed that SV-infected primary cortical neurons exhibited both apoptotic and necrotic morphological features and that uninfected neurons in the cultures also died. Antagonists of the N-methyl-d-aspartate (NMDA) subtype of glutamate receptors protected neurons from SV-induced death without affecting virus replication or SV-induced apoptotic cell death. These results provide evidence that SV infection activates neurotoxic pathways that result in aberrant NMDA receptor stimulation and damage to infected and uninfected neurons.